Analyzing User Continuance Intention and Continuance Behavior of Wondr by BNI with Utaut2 Model - Dania Samoda Renda; Anita Primaswari Widhiani; Febriantina Dewi (Publikasi Indonesia, 2026)
Digital transformation in the banking industry prompted BNI to launch Wondr by BNI in July 2024 as a replacement for its previous mobile banking application. Despite its advanced features, the application faces significant challenges in user adoption and user complaints regarding stability and functionality. This study aims to analyze the factors influencing continuance intention and continuance behavior of Wondr by BNI users, utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. A quantitative approach was employed through an online survey of 379 Wondr users. The data were analyzed using multiple linear regression and the PROCESS macro. The results show that Performance Expectancy, Social Influence, Price Value, and Habit have a positive and significant influence on Continuance Usage Intention (CUI). In turn, Continuance Usage Behavior (CUB) is significantly influenced by Continuance Usage Intention (CUI), Facilitating Conditions (FC), and Habit (HT). Age was also found to moderate the relationship between Hedonic Motivation and CUI. These findings provide managerial implications for BNI to encourage users to download and continue using the app, which prioritizes application stability, implements age-segmented strategies, increases rewards and promotions, adds Quick Actions and Do Again features on the home screen, introduces Group features, incorporates gamification and marketing segmentation features for younger users, adds clear micro-guidance, and provides live customer service chat.